Poly(2-propenoic acid) co- and terpolymers for dynamic membranes - Van Reenen, A. J.(Albert Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1988.